(untitled) (Journal of the Sociology and Theory of Religion, 2021)
Despite being less than a century old, the Church of Scientology, one of the most well-known and controversial new religious movements today, has a complex organizational scheme. This article presents, after a historical introduction, both the institutions that control the movement at the international level, as well as its ecclesiastical organization and associations dependent on community service. In addition, it ends with a review of this organizational reality in Spain.